Islamic Law Meets Minangkabau Customs: Navigating Forbidden Marriages in Tanah Datar - Fakhyadi, Defel; Samsudin, Muhammad Adib (El-Mashlahah, 2024)
Minangkabau community members in Tanah Datar have several prohibitions on marriage that must be obeyed and become standard rules because they contain sanctions of expulsion or ostracism. The prohibitions include marrying a cousin (father's sibling's child), marrying the ex-wife mamak (a man who is responsible for his children and nieces and nephews from the mother's side), and marrying the ex-wife's family. It indicates a contradiction between the provisions of Islamic law and customary law, which is very binding on the order of social life. The research aims to analyze the relationship between custom and Islamic law regarding the forbidden marriage that applies in Tanah Datar, which still maintains local culture and traditions. The method used empirical legal research with a socio-legal approach. Primary data was obtained using observation, interview, and documentation techniques, which were then analyzed using the maqashid sharia theory. The research showed that the Minangkabau community's prohibition on marriage in Tanah Datar is a customary rule that must be obeyed because it is a good habit ('urf) that aims to prevent damage to the social order in Minangkabau. Minangkabau society prioritizes the value of raso-pareso and friendly relationships between one person and another under the goals of marriage in Islamic law. These customary provisions are binding. If there is a violation, then customary sanctions are imposed in the form of exclusion, expulsion, and fines.